IMPACT OF TECHNICAL AND VOCATIONAL EDUCATION ON THE EMPLOYABILITY OF UNIVERSITY GRADUATES - Echeverría-Guzmán, Angel Yasmil; Rumbaut Rangel, Dayron; George-Reyes, Carlos Enrique; Valderrey Loroño, Michael Deivi; Tolozano Lapierre, Gabriela Nicole (LACCEI, 2025)
This study analyzes the impact of technical and vocational education on the employability of university graduates, considering their perception of integration and entry into the labor market during the period 2021–2024. Regarding the methodological approach, the study followed a positivist quantitative paradigm, with a non-experimental, field-based, and descriptive design. A total of 493 graduates from various academic programs across three universities in two countries were surveyed—specifically, from Ecuador: ITB and UBE; and from Venezuela: ULAC. Data were collected using a questionnaire with items distributed across three dimensions: quality of technical education, pre-professional practices, and technical experience and job placement. The findings reveal a significant gap between the education received and the realities of the labor market, highlighting the urgent need for institutions to redesign content and practices, increase resources, and adjust their educational offerings for more effective alignment.